Manajemen Keuangan Desa Sebagai Faktor Penentu Keberhasilan Pembangunan Desa (Studi Kasus di Desa Kanonang Empat Kec. Kawangkoan Barat) - Moniung, Tiara Mariana; Mandey, Jantje; Londa, Very (Sam Ratulangi University, 2015)
ABSTRACT : Management is a process of organization achievement by efforts from peoples.Management is a kind of special thought from leadership in order to attain the organization goals.The financial management of village is a factor who determined the successful of development andhelp process of the village development. Village financial is a rights and responsible in governmentorganized who can be valued with money included all the type of wealth who related with rightsand responsible of the village.Whereas who including the local government budget (LGB) village is the annual financialplanning of village government are investigated and approved together with the village governmentand LGB who determined by regulation of the village.Effectiveness in village financial process through good financial management system that willincrease the successful in village development. The organized of government village includeGovernment organized, Government affairs, and empowerment of villages communities.Village development is whole activities of development that run on village, include whole aspect ofthe entire citizen life that who operate in harmony with mutual cooperation. The Indicator ofsuccessful development village basically is a real repair in overall the life condition of society,because the construction is always a process of improvement of a state to a better state.Village development is a development that can be interpreted as a conscious efforts in aseries of activities to achieve a change from bad situation to better situation performed by a certainpeople in the country.Key Word : Financial Management, Development